2007
DOI: 10.1007/s00402-007-0366-z
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering of tendons and ligaments by human bone marrow stromal cells in a liquid fibrin matrix in immunodeficient rats: Results of a histologic study

Abstract: Injection of human BMSC in a fibrin glue matrix appears to lead to more mature tissue formation with more regular patterns of cell distribution. Advantages of this "in-vivo" tissue engineering approach are a homogenous cell-matrix mixture in a well-known and approved biological matrix, and simple, minimally-invasive application by injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…The results of these reports have not been consistent, with some studies demonstrating that fibrin scaffolds increased cell viability, proliferation, or differentiation 18,20 and others showing that fibrin may adversely affect these parameters 16,18,20 . An in vitro tendon repair model showed that fibrin gel, acting as a carrier of growth differentiation factor-5 (GDF-5)-treated muscle-derived stem cells, enhanced tendon healing, as evaluated both mechanically and histologically, compared with a collagen gel at both two weeks and four weeks 21 .…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The results of these reports have not been consistent, with some studies demonstrating that fibrin scaffolds increased cell viability, proliferation, or differentiation 18,20 and others showing that fibrin may adversely affect these parameters 16,18,20 . An in vitro tendon repair model showed that fibrin gel, acting as a carrier of growth differentiation factor-5 (GDF-5)-treated muscle-derived stem cells, enhanced tendon healing, as evaluated both mechanically and histologically, compared with a collagen gel at both two weeks and four weeks 21 .…”
mentioning
confidence: 83%
“…A number of studies have been performed to investigate the effect of fibrin scaffolds seeded with stem cells with and without growth factor augmentation 16,[18][19][20] . The results of these reports have not been consistent, with some studies demonstrating that fibrin scaffolds increased cell viability, proliferation, or differentiation 18,20 and others showing that fibrin may adversely affect these parameters 16,18,20 .…”
mentioning
confidence: 99%
“…The ideal carrier system should prevent cell membrane rupture during the injection process; create increased tissue integration through fast in situ self-assembly; facilitate long-term cell survival and functionality maintenance; and allow spatiotemporal release of the cargo [222][223][224][225][226][227][228][229][230][231]. Preclinical data using either collagen [232] or fibrin [233] hydrogels have demonstrated improved mechanical properties, histological scores, tissue integration and restored functionality using TCs and various stem cell populations [234,235], however clinical use of injectable cell/hydrogel systems is still to be realised.…”
Section: Delivery Of Viable Cell Populationsmentioning
confidence: 99%
“…In vitro studies have shown that MSCs can differentiate into several cell types, including adipocytes [2], chondrocytes [3], osteoblasts [4], and ligament cells [5]. When induced in a defined adipogenic medium, most hMSCs differentiate into adipocytes.…”
Section: Introductionmentioning
confidence: 99%